Neuroendocrine Role for VGF - Lewis, Jo E.; Brameld, John M.; Jethwa, Preeti H. (Frontiers in Endocrinology, 2015)
The vgf gene (non-acronymic) is highly conserved and was identified on the basis of its rapid induction in vitro by nerve growth factor, although can also be induced by brain derived neurotrophic factor, and glial derived growth factor. The VGF gene gives rise to a 68kDa precursor polypeptide which is induced robustly, relatively selectively and is synthesized exclusively in neuronal and neuroendocrine cells. Post-translational processing by neuroendocrine specific pro-hormone convertases in these cells results in the production of a number of smaller peptides. The VGF gene and peptides are widely expressed throughout the brain, particularly the hypothalamus and hippocampus, and in peripheral tissues including the pituitary gland, the adrenal glands and the pancreas, and in the gastrointestinal tract in both the myenteric plexus and in endocrine cells. VGF peptides have been associated with a number of neuroendocrine roles and in this mini-review we aim to describe these roles to highlight the importance of VGF as therapeutic target for a number of disorders, particularly those associated with energy metabolism, pain, reproduction and cognition.